Negotiating the ambivalent construction of 'coloured' identity, in relation to the work of Malika Ndlovu and the Cape Town-based Black Women's Writers Collective, WEAVE - Tobin, Fiona (Department of English Language and Literature, 2014)
Bibliography: leaves 51-53.